PEREMPUAN KRISTEN JAWA DAN KEWIRAUSAHAAN PENDETA: NEGOSIASI ANTARA IDENTITAS DAN INSTITUSI KEAGAMAAN - Adi, Suwarto (Universitas Kristen Satya Wacana, 2019)
This paper aims at tracing the negotiation process between self-identity and institutional image of the church among Javanese Christian women, and makes use of a short biography as a narrative. It based on such a biography explored that in order to meet family need sufficiently, a rural pastor should not implement an entrepreneurial project, either personally or organizationally. If an entrepreneurial project inevitably is to do, the Javanese Christian women emphasizing that pastors’ entrepreneurial should go around the ministry they are doing, for instance, making books or teaching in a Christian school or seminary. This paper also argues that the pastors’ family that are in a harmony and self-sufficient is a social gate to show the institutional image of church in society. Due to all Javanese Christian women are having jobs and source of economic income, all of them are brave to negotiate with the church to sustain keep the job that they had been pursued, and involve partly in the church activity. This paper concludes that a simple life that the women showing on their life, and it carried out voluntarily is a kind of personal commitment and calling to support the husband ministry as a pastor.